Modeling of lithium ion battery with nonlinear transfer resistance - Yao, L. W. (IEEE, 2011)
This paper discusses the Lithium Ion battery modeling by using equivalent circuit model with nonlinear transfer resistance. The modeling is done by using MATLAB/Simulink. A constant current pulse test is used to extract the model's parameters and the procedures are presented in details. Then the voltage responses of the conventional model, proposed model and MATLAB Li-ion cell model are compared. From the comparison, it reveals that the proposed model producing a better accuracy compared to conventional equivalent circuit model.